Pengaruh Financial Leverage, Net Profit Margin, Likuiditas dan Corporate Governance terhadap Earnings Management pada Perusahaan-Perusahaan Otomotif (Studi di Bursa Efek Indonesia Tahun 2011-2015) - Isti Istiqomah; Michael Hadjaat; Maryam Nadir (Jurnal Ilmu Manajemen Mulawarman (JIMM), 2018)
This research aims to examine and analyze the influence of financial leverage, net profit margin, liquidity and corporate governance on earnings management. Financial leverage is measured by debt to asset ratio (DAR), liquidity is measured by current ratio (CR) and corporate governance is measured by managerial ownership. Discretionary accrual is the proxy of earnings management. The analytical tool that used to support the calculation is multiple linear regression which processed by SPSS Statistics Program version 22. This research used 7 automotive companies listed in Indonesia Stock Exchange, selected using purposive sampling method. The research was conducted with 35 data from 2011-2015. The result of this research indicates that net profit margin, liquidity, and managerial ownership have no significant effect on earnings management while, financial leverage has a negative and significant effect on earnings management. It means that automotive companies with high leverage will restrict the practice of earnings management.Keywords: Earnings Management, Debt to Asset Ratio, Net Profit Margin, Current Ratio, Managerial Ownership.